2016
DOI: 10.1002/fuce.201500113
|View full text |Cite
|
Sign up to set email alerts
|

Detailed Multi‐dimensional Modeling of Direct Internal Reforming Solid Oxide Fuel Cells

Abstract: Fuel flexibility is a significant advantage of solid oxide fuel cells (SOFCs) and can be attributed to their high operating temperature. Here we consider a direct internal reforming solid oxide fuel cell setup in which a separate fuel reformer is not required. We construct a multidimensional, detailed model of a planar solid oxide fuel cell, where mass transport in the fuel channel is modeled using the Stefan‐Maxwell model, whereas the mass transport within the porous electrodes is simulated using the Dusty‐Ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 61 publications
0
9
0
1
Order By: Relevance
“…For heat transfer, the assumption commonly made is that the radiation effect in the stack is negligible [16]. Considering that heat transfer occurring in SOFC is significantly in conduction or convection mode, the effect of radiation is usually not considered during simulation, especially in planar SOFCs as the amount is comparatively smaller [22][23][24][25][26]. Moreover, in single planar SOFC, heat radiation does not affect the cell.…”
Section: Assumptions In Sofc Modelingmentioning
confidence: 99%
“…For heat transfer, the assumption commonly made is that the radiation effect in the stack is negligible [16]. Considering that heat transfer occurring in SOFC is significantly in conduction or convection mode, the effect of radiation is usually not considered during simulation, especially in planar SOFCs as the amount is comparatively smaller [22][23][24][25][26]. Moreover, in single planar SOFC, heat radiation does not affect the cell.…”
Section: Assumptions In Sofc Modelingmentioning
confidence: 99%
“…Хотя вопрос механизмов реакций риформинга остается открытым и на данный момент не существует единой теории процессов кинетики внутреннего риформинга в ТОТЭ [14], из имеющихся данных можно заключить, что частичное окисление метана рассматривается как более быстрая реакция, нежели MSR [15]. WGS реакция является значительно более быстрой по сравнению с MSR [11,16]. Кроме того, из уравнения Аррениуса известна следующая зависимость скорости реакции r, моль/м 3 •с от температуры:…”
Section: Extended Abstractunclassified
“…), and its low price [2]. However, SOFC operates under high-temperature conditions for a long time, and factors such as uneven temperature distribution inside the cell due to strong endothermic reforming reactions, carbon deposition from hydrocarbon fuel cracking, repeated oxidation-reduction in porous nickel-based anodes, and mismatch of thermal expansion coefficients of the constituent materials further aggravate the instability of cell life [3][4][5][6][7]. In addition, there are complex multi-phase, multi-scale and multi-field coupled transfer processes in the pores and three-phase boundary sites of micro/nanoporous electrodes where electrons, ions, and gases are combined in SOFC.…”
Section: Introductionmentioning
confidence: 99%
“…There is a local mismatch between the endothermic methane steam reforming reaction rate and the exothermic electrochemical rate [8]. Tseronis et al [3] conducted several parametric studies on the direct internal reforming SOFC employing numerical simulation. It is shown that the cooling effect of the methane steam reforming reaction leads to a significant local temperature drop near the anode inlet and a large temperature difference inside the SOFC.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation